Effects of Chemical Bonding Animation-Based Instruction on Secondary School Students’ Academic Achievements: A Quasi-Experimental Study - Yohanna Ogbu Egiri; Joseph Izang Azi; Aminu Muhammad Abdullahi (Journal of Educational Research and Practice, 2026)
Understanding chemical bonding presents a persistent challenge for secondary school students due to the abstract and subatomic nature of the concepts involved. This study examined the effectiveness of an animation-based instructional package in improving students' understanding of chemical bonding. A quasi-experimental pretest–posttest design was employed involving 160 Senior Secondary School II students drawn from eight public secondary schools in Nigeria. Students were assigned to either an experimental group that received animation-supported instruction or a control group that received conventional instruction. Data were collected using a researcher-developed multiple-choice achievement test and analyzed using independent-samples t-tests and one-way analysis of variance. The results indicated that students exposed to animation-based instruction achieved significantly higher posttest scores than those taught using conventional methods across all schools. In addition, no significant differences were found among the experimental groups across schools, suggesting that the instructional effect of the animation package was consistent across different educational contexts. These findings provide empirical evidence that animation-based instruction can effectively support students' understanding of abstract chemistry concepts and highlight its potential as a pedagogical tool for improving secondary school chemistry education.